The immorality of Christianity : does Christianity contain the best moral values available? - Jón Birkir Bergþórsson 1990- (2014)
Iceland has been a Christian country for over a thousand years. The conventional assumption is that Christianity is the best set of morals available to us. Does Christianity contain the best moral values? Religion has in the past had a monopoly over ethical matters and as such it’s important for it to be ready to face inquisitions over its justification. We humans are unique in the animal kingdom because of our intelligence, our ability to empathize and to make complicated ethical decisions. So should we settle for the Bible as our ethical guideline, written hundreds of years ago or is it time to rethink our heritage of Christian values? The issue of ethical behavior concerns all of society, whether it’s inculcated through written laws or unwritten ones. Because of this I feel that these debates are of paramount importance for all of us. In this dissertation I’m going to argue that Christian ethics are in many ways immoral. Specifically I’m going to challenge the ethical doctrine presented in the New Testament, the supposed connection between faith and morality and give my insight into the debate on the role that Christianity should play in our school. Because this is a philosophical dissertation, I try to take responsibility in not misrepresenting Christianity which is why this dissertation includes an interview with Rev. Hildur Eir Bolladóttir and my response to what she has to say. Ísland hefur verið kristið land í meira en þúsund ár. Það er almennt ályktað að kristindómurinn feli í sér allra bestu siðgildin sem eru möguleg. Inniheldur kristinfræði besta siðfræðiboðskapinn? Trúarbrögð hafa í gegnum tíðina einokað siðfræðina og þess vegna er svo mikilvægt að gagnrýna þau, til þess að þau geti réttlætt stöðu sína. Við mennirnir erum einstakir í dýraríkinu vegna gáfna okkar, getu okkar til þess að hafa samúð með öðrum og til þess að taka flóknar siðfræðilegar ákvarðanir. Ættum við að sætta okkur við Biblíuna sem okkar siðfræði leiðsögn, rit sem var skrifað fyrir hundruðum ára eða er kominn tími til þess að við ...